POSITION OF CHILDREN OUT OF MARRIAGE IN PERSPECTIVE OF PROGRESSIVE ISLAMIC LAW - Ma'arif, Toha; Faisal, F.; Khairuddin, K.; Baihaqi, Yusuf (SMART: Journal of Sharia, Traditon, and Modernity, 2022)
Children born out of marriage are children born from marriages carried out according to their respective religions and beliefs. This understanding shows the existence of marriage, and if it is carried out according to the Islamic religion, then such a marriage is valid in the perspective of Islamic fiqh as long as it meets the requirements and pillars. Regarding to the position of children out of marriage, in 2012, the Constitutional Court issued a decision related to this matter which then raised pros and cons from various parties, both from legal practitioners, academics, the Indonesian Ulema Council, and even the community. Based on it, this research would like to examine more deeply related to the legal position of children out of wedlock in Indonesian legislation in the perspective of Progressive Islamic law. The type of research used is normative-empirical legal research using primary and secondary data, data analysis using qualitative descriptive and drawing conclusion using deductive thinking. The results showed that children out of marriage in the perspective of progressive Islamic law are children out of marriage have a kinship relationship with their father if born at least six months after marriage or within a grace period of four years after the marriage broke up provided it is evident that within four years their mother didn't excrete.